Company Size as a lever between Capital Structure and Financial Performance on Firm Value - Elisa Sukoco; Kadarusman Kadarusman (Jurnal Riset Akuntansi Terpadu, 2023)
This research has the purpose to analyze the effect of capital structure and financial performance on firm value moderated by firm size. The population of this research is financial sub-sector companies listed on the Indonesia Stock Exchange. The sample taken was 22 financial sub-sector companies that experienced profits in 2020-2022 which were selected through purposive sampling technique. The analysis method uses multiple linear regression and moderated regression analysis. The results of the analysis show that capital structure has no effect on firm value, financial performance has a positive and significant effect on firm value, company size is can't moderate the effect of capital structure on firm value, but company size is can to moderate the effect of financial performance on firm value. The limitations experienced are that there are companies that experienced losses in 2020-2022. The results of this research are expected to be a consideration for investors in investing.